Traumatic Globe Displacement into Anterior Cranial Fossa - Patricia Ann John; Sylves Patrick; Mohtar Ibrahim; Adil Hussein (2020)
A 64-year-old Malay gentleman alleged occupational injury when a malfunctioned metal hydraulic door hit on his face while unloading sand from his tipper-truck. Post-trauma, he complained of right eye (RE) pain and total loss of vision. On examination, noted RE visual acuity was unable to be assessed and left eye (LE) was 6/24 with pinhole 6/9. No eyeball could be seen in the right socket with superior orbital rim step deformity and left periorbital haematoma. Computed tomography scan of the brain and orbit confirmed displaced right eye globe into the right anterior cranial fossa with right and left multiple orbital wall fractures. He then underwent successful right eye globe repositioning. Traumatic orbital roof fracture is a rare condition. Repositioning of the eye globe was done to salvage the eye globe for a cosmetic reason and to avoid localised inflammatory reaction at the anterior cranial fossa.